The Single Presence Policy for Rural Banks - Bachtiar Marbun (Journal of Business, Social and Technology, 2026)
Background: Indonesian banking regulation has undergone significant structural transformation with the enactment of OJK Regulation No. 12/POJK.03/2020. This regulatory shift raises critical legal questions about its implications for Rural Bank institutions. Objective: This research aims to understand and examine the single presence policy for Rural Banks, which is predicted to be implemented, and to determine the consequences of the single presence policy regulation after the issuance of the Commercial Bank Consolidation POJK. Methods: The research methods applied include qualitative research with normative legal methods, employing statute and conceptual approaches to analyze primary legal materials, including Bank Indonesia Regulations, OJK Regulations, and the P2SK Law (Law No. 4/2023). Results: The single presence policy for Rural Banks is predicted to be implemented with the aim of increasing banking stability, resilience, and competitiveness at the national level, as well as facilitating digital revitalization in the financial industry. Regarding the harmonization of bank control regulations through controlling shareholders, the Commercial Bank Consolidation POJK also regulates changes related to the minimum capital requirements for bank tier thresholds. The current core capital requirements are as regulated in Article 147, paragraph (1) of the Republic of Indonesia Financial Services Authority Regulation Number 12/POJK.03/2021 concerning Commercial Banks, which are grouped into 4 (four) KBMI. Conclusion: The emergence of the single presence policy is unsuitable and irrelevant for banking, especially for BPR, considering that the history of the formation of BPR, which aimed to help people in rural areas, is contrary to the single presence policy.